Iron‐related toxicity effects of single‐walled carbon nanotubes in human placental cells (BeWo) investigated by X‐ray fluorescence microscopy. (18th December 2018) - Gianoncelli, Alessandra; Cammisuli, Francesca; Altissimo, Matteo; Salomé, Murielle; Radillo, Oriano; Ricci, Giuseppe; Giordani, Silvia; Rizzardi, Clara; Pascolo, Lorella
Abstract : As the prospect of human beings exposed to new nanomaterials increases, there are growing concerns about the foetal exposure and effects of such nanomaterials during pregnancy. Among others, due to their ample usage, it becomes urgent to address the vulnerability of the human placental barrier to carbon nanotubes (CNTs). Recently, by applying a combination of advanced synchrotron‐based X‐ray microscopy and X‐ray fluorescence (XRF) techniques, we demonstrated that raw single‐walled CNTs (SWCNTs) may cause an asbestos‐like iron‐related toxicity in mesothelial (MeT5A) cells. This work shows the results obtained with the same approach and experimental conditions in human choriocarcinoma (BeWo) cells as a placental model. XRF microscopy in mild and soft X‐ray regimes was used to map the distribution of P, S, Ca, and Fe in exposed and control cells, whereas absorption and phase‐contrast imaging (soft X‐ray microscopy) provided simultaneous morphological information. The findings show that exposure to SWCNTs affects cell viability and causes a small increase in intracellular iron content, further confirmed by the stimulation of the ferritin protein. It is interesting to note that the iron changes are negligible when highly purified SWCNTs are used. In all tested conditions, including exposure to iron sulfate, the iron accumulation or ferritin increase was much lower in BeWo cells than in MeT5A ones, suggesting a different iron metabolism and possibly a lower vulnerability of the placental barrier to iron‐rich nanomaterials.